1991
DOI: 10.1111/j.1365-2125.1991.tb03862.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraindividual variability in the concentration‐effect (sedation) relationship of flunitrazepam.

Abstract: 4 The results in young healthy subjects suggest that the present dosage recommendations for temporary insomnia (1-2 mg) may be inappropriate; the dose can probably be reduced to 0.5 mg in some patients to achieve moderate sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…These results are in agreement with other studies (Grahn6n et al 1991;Ingum et al 1992;Rush et al 1993a, b). Flunitrazepam 2 mg produced the greatest sedation, followed by triazolam 0.50 mg, triazolam 0.25 mg, and flunitrazepam 0.50 mg.…”
Section: Discussionsupporting
confidence: 96%
“…These results are in agreement with other studies (Grahn6n et al 1991;Ingum et al 1992;Rush et al 1993a, b). Flunitrazepam 2 mg produced the greatest sedation, followed by triazolam 0.50 mg, triazolam 0.25 mg, and flunitrazepam 0.50 mg.…”
Section: Discussionsupporting
confidence: 96%
“…In order of potency, ßunitrazepam 4 mg and triazolam 0.75 mg produced similar impairment, and produced the greatest sedation followed by triazolam 0.50 mg and ßunitrazepam 2 mg. These results are in agreement with other studies in which the e¤ects of these compounds were tested in di¤erent populations (Evans et al 1990;Grahnén et al 1991;Ingum et al 1992Ingum et al , 1994Rush et al 1993a,b;Farré et al 1996).…”
Section: Discussionsupporting
confidence: 94%
“…When compared with the published flunitrazepam pharmacokinetic parameters, the mean half‐life was close to the values reported in adults (20 to 36 hours, 11 25 ± 6 hours, 12 29 ± 11 hours, 3 22.9 ± 6.4 hours, 7 and 25 ± 11 hours 8 ) but longer than the values published in older children (11.8 ± 3.7 hours 4 and 3.98 ± 4.8 hours 9 ). The area under the curve normalized for a same dose was similar to that described in adults by Kanto et al 3 No influence of age on flunitrazepam pharmacokinetics was shown in previous studies that involved elderly poor‐risk patients 7 and healthy adult surgical patients 3 , 8 .…”
Section: Discussionsupporting
confidence: 78%